Manajemen Literasi Dalam Mendorong Inovasi - Tenriwati; Sri Rahayu (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Hospital expansion is driven by demand for health services due to the uneven health facilities in Bekasi Regency. This study aims to analyse the development strategy of Putra Medika Hospital using TOWS Analysis and Exploratory Mixed Methods. This research method is mixed. The qualitative phase began with in-depth interviews with the management of the Putra Medika Group Clinic to identify strengths, weaknesses, opportunities and threats. This qualitative data became the foundation for formulating the TOWS matrix. Then, the quantitative phase in the form of a survey was conducted on prospective patients and stakeholders, validating the qualitative findings and measuring market preferences. The qualitative participants were 22 people while the quantitative sample was 40 people. The results of the TOWS analysis show that Putra Medika has internal strengths to capitalise on market opportunities, but also needs to overcome weaknesses and manage competitor threats. In conclusion, Putra Medika Clinic management must integrate the findings of internal and external factors to produce concrete strategic recommendations for hospital development. These include optimisation of superior services, effective marketing strategies, and risk mitigation. The implications of this research offer practical guidance for Putra Medika's management so that expansion in Bekasi can be carried out in a sustainable and competitive manner.